Ministry to the sick and dying in the Late Medieval Church - Izbicki, Thomas M. (Catholic University of America Press, 2023)
Intro -- Contents -- Introduction -- List of Abbreviations -- 1. Ministry to the Sick -- 2. Sickbed Confession -- 3. Sickbed Communion -- 4. Anointing of the Sick -- 5. The Hour of Death -- Epilogue:The Reformation, Tridentine Reforms, and Missions Abroad -- Select Bibliography -- Index.